Functional characterization of a hybrid human-mouse interferon gamma receptor: evidence for species-specific interaction of the extracellular receptor domain with a putative signal transducer. - Hemmi, S (1992)
The human interferon gamma (IFN-gamma) receptor expressed in mouse cells displays binding properties indistinguishable from those of the resident receptor on human cells. Still, mouse cells expressing the human IFN-gamma receptor remain insensitive to human IFN-gamma. It is widely accepted that at least one species-specific cofactor encoded within human chromosome 21 is required for signal transduction. To define structural domains of the human IFN-gamma receptor responsible for this species-specific interaction, a hybrid between the human and the murine receptor was constructed and expressed in mouse L929 cells or in mouse L cell-derived SCC16-5 cells, which contain human chromosome 21. This hybrid receptor, which consisted of the extracellular domain of the human IFN-gamma receptor and the transmembrane and cytoplasmic domains of the murine IFN-gamma receptor, was found to bind human IFN-gamma with high affinity. However, only SCC16-5 cells expressing the human/mouse hybrid receptor were responsive to human IFN-gamma as revealed by enhanced expression of major histocompatibility complex class I antigens, induction of the transcription factor IRF-1, and induction of a partial antiviral state. These findings strongly suggest that IFN-gamma-mediated signal transduction requires a species-specific interaction of the extracellular portion of the known ligand-binding IFN-gamma receptor chain with an additional, presumably membrane-anchored receptor subunit.